1999
DOI: 10.1200/jco.1999.17.1.230
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Irradiation Alone for Clinical Stage I-II Hodgkin's Disease: Long-Term Follow-Up and Analysis of Prognostic Factors in 261 Patients

Abstract: These results support the use of MRT alone in patients with favorable CS I HD and CS I-II HD with lymphocyte-predominant histology. The remainder of patients with CS I-II HD require more intensive treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In a previous study of mantle-field RT for patients with clinical Stage I and II Hodgkin lymphoma, we reported that patients diagnosed with LPHL had a 10-year freedom from progression rate of 80% compared with 50% for patients diagnosed with classic Hodgkin lymphoma, a difference that was significant after adjusting for other prognostic factors. 17 Studies of earlystage follicular NHL treated with RT alone have reported durable remission rates of 40 -50%. 27,28 These results suggest that LPHL has a natural history that is distinct from both classic Hodgkin lymphoma and follicular NHL.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study of mantle-field RT for patients with clinical Stage I and II Hodgkin lymphoma, we reported that patients diagnosed with LPHL had a 10-year freedom from progression rate of 80% compared with 50% for patients diagnosed with classic Hodgkin lymphoma, a difference that was significant after adjusting for other prognostic factors. 17 Studies of earlystage follicular NHL treated with RT alone have reported durable remission rates of 40 -50%. 27,28 These results suggest that LPHL has a natural history that is distinct from both classic Hodgkin lymphoma and follicular NHL.…”
Section: Discussionmentioning
confidence: 99%
“…17,27 Thus even if the current series included a proportion of patients who currently would be classified with classic Hodgkin lymphoma or follicular NHL, it is unlikely that we overestimated the results of RT for LPHL. Another potential limitation of this study was the difficulty in distinguishing reliably between the progression of LPHL and the development of a new NHL.…”
Section: 11mentioning
confidence: 95%
See 1 more Smart Citation
“…Because less than 33% of deaths among patients with Stage I-II LPHD are due to Hodgkin disease, compared with 50% of deaths among patients with CHD, 5 and because LPHD uncommonly involves the paraaortic lymph nodes or the spleen on presentation, 4,9,10 some groups 26,27 have suggested that mantle radiotherapy alone is the preferred treatment for patients with VF or F LPHD. 7,28 For example, Backstrand et al 28 in Boston have suggested that mantle irradiation alone may be preferable from a quality-oflife standpoint and may reduce the risk of solid tumors compared with STNI.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is commonly used for treatment of HD 8 but other options include chemotherapy, combined modality treatment and, in selected cases, postoperative observation only. 9 In cases of HD involving the supradiaphragmatic lymph nodes the radiotherapy technique commonly implemented is the mantle technique.…”
Section: Treatment Optionsmentioning
confidence: 99%